Motivations, perceived risk, and tampering of XTAMPZA ER and abuse-deterrent opioid drugs - Hannah L. Burkett; Richard C. Dart; Joshua C. Black (PLoS ONE, 2025)
Abuse deterrent formulation (ADF) products are designed to prevent people from tampering with medication, especially with the intention to misuse or abuse the product. While clinical results support the efficacy of ADF products in controlled settings, little is known about how people use and abuse them in the real world. The objective of this research was to describe tampering behavior and perceived risk among U.S. adults who report non-medical use (NMU) of XTAMPZA® ER, a novel ADF extended-release opioid, and comparable products. A cross-sectional survey was conducted in 2021 and 2022 among adults who reported NMU of oxycodone or hydrocodone products in the past year. To compare use patterns and tampering behavior to XTAMPZA® ER, three similar opioid products were also assessed. Participants who reported NMU of an eligible drug were asked why they used it, how they tempered with it, and what other drug-related behaviors they engaged in. A total of 628 participants were recruited. A total of 56 (8.92%) reported NMU of XTAMPZA® ER in the past year, 256 (40.8%) reported NMU of other ADF ER oxycodone/hydrocodone, 459 (73.1%) reported NMU of non-ADF ER oxycodone/hydrocodone, and 225 (35.8%) reported NMU of IR oxycodone. Non-ADF ER oxycodone/hydrocodone was the most used. Those who reported NMU of XTAMPZA® ER had more severe drug use profiles, including higher scores on the 10-item Drug Abuse Screening Test (DAST-10) and higher prevalence of concomitant and illicit drug use. Overall, 3.7% tampered with XTAMPZA® ER, 12.9% tampered with other ADF ER oxycodone/hydrocodone, 16.0% tampered with non-ADF ER oxycodone/hydrocodone, and 10.7% tampered with IR oxycodone. U.S. adults who reported tampering with XTAMPZA® ER or a comparable product frequently did so for therapeutic reasons, most commonly “to swallow the pill more easily” and “to improve the pain relief from the pill.” They also viewed tampering with products they used as less risky than tampering with products they did not use. Tampering with XTAMPZA® ER was uncommon compared to other drugs but more common as a proportion among those who used XTAMPZA® ER. This is, potentially because those using XTAMPZA® ER had other markers of severe, problematic drug use.